Examining The Mediating Role of Tax Avoidance in the Determinants of Earnings Management in Manufacture Listed Companies - Paulus, Hendro; Tarmidi, Deden (Baca Dulu Publisher, 2025)
This study examines the effect of managerial ownership, transfer pricing, and company size on earnings management, with tax avoidance as a mediating variable, in manufacturing companies listed on the Indonesia Stock Exchange during 2020-2023. This research uses a quantitative approach with a causal-comparative design. The purposive sampling method was used to select 42 companies, resulting in 168 company-year observations. The data were analyzed using panel data regression with Random Effect Model (REM) based on Chow, Hausman, and LM tests. The results show that only transfer pricing has a significant and positive effect on earnings management, while managerial ownership and firm size do not show a significant effect. In addition, tax avoidance significantly strengthens the relationship between transfer pricing and earnings management but weakens the relationship between managerial ownership and firm size. These results imply that firms tend to manipulate earnings through strategic transfer pricing, especially if accompanied by aggressive tax avoidance. The novelty of this study lies in integrating tax avoidance as a mediating factor in the agency theory framework to explain earnings management practices in emerging markets such as Indonesia.